Has the optimal tariff theory ever been applied in the real world? - Han, Wang (Kansas State University, 2014)
Terms-of-trade argument (the optimal tariff theory) refers that a country with market power can gain national welfare when they impose a tariff for foreign exports and generate welfare at the expense of foreign trade partners. This argument has been long-term applied as an assumption in many theoretical trade models. Feenstra (2004) shows that the theoretical optimal tariff is equal to the inverse foreign export supply elasticity which implies if we can get the value of inverse export elasticity for each good then we can set up the optimal tariff to maximized our national welfare. Compared with the development in theory, the progress in the empirical study of terms-of-trade argument has been a bit stagnant until recent years. Christian Broda, Nuno Limão and David Weinstein (2008) show us an important empirical evidence that countries use market power when they set up tariff in their non-cooperative trade policy. And they estimate both import demand elasticity and export supply elasticity at the four-digit Harmonized System level by using 16 countries’ trade data and production data. In this report, we firstly introduce the theoretical basis of optimal tariff. Then we will discuss the contributions of Broda et al (2008) and other economists’ empirical findings of optimal tariff theory which applies Broda, Limão and Weinstein’s estimates of elasticities
Keywords: Economics; The Optimal Tariff; Terms of Trade; Tariff; Economics (0501)